Inquiry Learning Model in Natural Sciences Subjects at Al Amin Islamic Secondary School Kemamam Terengganu - Hanafi Arbi Wiranata; Melly Novalia (Journal of Sustainable Education, 2025)
The Inquiry learning model is an approach that emphasizes the active involvement of students in the process of discovering and building understanding of scientific concepts. This study aims to analyze the effectiveness of the Inquiry learning model in improving students' understanding and critical thinking skills in Natural and Social Sciences (IPAS) subjects in Elementary Schools. The research methods used are literature studies and classroom experiments involving students as research subjects. The results of the study indicate that the application of the Inquiry model can increase students' learning motivation, strengthen critical thinking skills, and encourage in-depth exploration of concepts. In addition, this model also helps students develop problem-solving skills and group collaboration. Thus, the Inquiry learning model is recommended as an effective approach in IPAS learning in Elementary Schools to improve the quality of learning and student learning outcomes.